Correlação linear e espsacial entre a produtividade de feijão e a porosidade de um Latossolo Vermelho de Selvíria (MS) - Megda, Marcio Mahmoud [UNESP]; Carvalho, Morel de Passos e. [UNESP]; Vieira, Michele Xavier [UNESP]; Andreotti, Marcelo [UNESP]; Pereira, Elaine Cristina [UNESP] (Sociedade Brasileira de Ciência do Solo, 2008)
Soil porosity influences plant development since root growth and crop yield are determined by the root depth. The objective of this study was to investigate the linear and spatial variability and correlations between common bean yield and soil porosity. The bean grain yield of the irrigated cultivar Carioca IAC was analyzed in the growing season 2004/2005, in Selviria-MS, as well as macroporosity (MA), microporosity (MI) and total porosity (TP), in a Dystroferric Red Latosol, at four depths: 1 (0.0-0.10 m), 2 (0.10-0.20 M), 3 (0.20-0.30 m) and 4 (0.30-0.40 m). Soil and plant data were collected in a geostatistical grid with 135 points spaced 10 m apart, covering an area of 50 x 150 m. The data of the studied attributes did not vary randomly and the values were intermediate to low. They followed well-defined spatial standards, reaching between 11.70-104.40 m. on the other hand, the linear correlation between the plant and soil attributes was low, due to the high number of observations. Grain yield had the best linear correlations with MA1b, MI1 and TP3. From the spatial point of view, the inverse correlation between PG and #TP2 was outstanding. At the sites where #TP2 diminished (0.030-0.045 m(3) m(-3)) the yield varied from 2,173 to 3,529 kg ha(-1) and where it increased (0.045-0.076 m(3) m(-3)), the yield was between 1,630 and 2,173 kg ha(-1). Therefore, the total soil porosity, evaluated in the 0.10-0.20 m layer (#TP2), indicated the importance of the contact root/soil and was in turn a satisfactory indicator of soil physical quality, with a view to the grain yield of irrigated common bean.

A porosidade do solo exerce grande influência sobre o crescimento e desenvolvimento vegetal, uma vez que o crescimento das raízes, tal como a produtividade das culturas, é limitado pela profundidade que atingem. Portanto, o objetivo deste trabalho foi estudar a variabilidade espacial e as correlações lineares entre a produtividade de feijão e a porosidade do solo. No ano de 2004/2005, no município de Selvíria, MS, foram analisadas a produtividade de grãos de feijão (PG), cultivar IAC Carioca, irrigado, a macroporosidade (MA), a microporosidade (MI) e a porosidade total (PT) do solo em quatro profundidades: 1 (0,0–0,10); 2(0,10–0,20); 3(0,20–0,30) e 4(0,30–0,40 m), num Latossolo Vermelho distroférrico. As amostras de solo e planta foram coletadas em uma malha geoestatística com 75 pontos espaçados de 10 x 10 m, mais 60 pontos de quatro malhas de refinamento numa área de 50 x 150 m. Os atributos estudados, além de não terem variado aleatoriamente, apresentaram média e baixa variabilidades. Seguiram padrões espaciais bem definidos, com alcances entre 11,70 e 104,40 m. A correlação linear entre o atributo da planta e os do solo, em função do elevado número de observações, foi baixa. As de melhor correlação linear com a PG foram a MA1, MI1 e a PT3. Entretanto, do ponto de vista espacial, houve excelente correlação inversa entre a PG e a #PT2. Assim, nos sítios onde a #PT2 diminuiu (0,030–0,045 m3 m-3 ), a PG variou entre 2.173 e 3.529 kg ha-1. Já naqueles onde aumentou (0,045–0,076 m3 m-3 ), a PG ficou entre 1.630–2.173 kg ha-1. Assim, a porosidade total do solo, quando avaliada na camada de 0,10–0,20 m (#PT2), indicou a importância do contato raiz/solo e, de modo inverso, apresentou satisfatório indicador da qualidade física do solo estudado, quando destinado à produtividade de grãos de feijão irrigado.
Linear and spatial correlation between common bean yield and porosity of a Red Latosol in Selviria (MS), Brazil
Keywords: spatial variability; soil management; no-tillage; Phaseolus vulgaris L.